(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Reliability of electrical connectors is increasingly critical in modern automotive systems, particularly as the industry transitions toward fully electric vehicles with dense sensor networks and expanded data processing needs. Failures in connector interfaces can lead to severe system malfunction, equipment damage, or safety hazards. Among the various environmental and mechanical stressors that affect connector performance, electrical contact degradation, often evidenced by increased contact resistance, remains a primary concern. This study investigates the mechanisms and progression of contact degradation through controlled thermal aging of fabricated samples. ZrCu alloy coatings were deposited onto copper-clad laminates using cathodic arc technology to create representative contact interfaces. The evolution of contact resistance was monitored under low-current, low-voltage conditions to capture early-stage degradation effects. Results show a clear increase in resistance with aging, confirming the sensitivity of contact performance to factors such as oxidation, temperature exposure, and surface contamination. Additionally, the applied contact load was found to influence the effective contact area, thereby affecting overall resistance behavior.